Energy frameworks: insights into interaction anisotropy and the mechanical properties of molecular crystals. Issue 18 (19th December 2014) - Turner, Michael J.; Thomas, Sajesh P.; Shi, Ming W.; Jayatilaka, Dylan; Spackman, Mark A.
Abstract : Energy frameworks provide an approach to understanding crystal packing by combining quantitative intermolecular interaction energies with qualitative and appealing graphics. Abstract : We present an approach to understanding crystal packing via 'energy frameworks', that combines efficient calculation of accurate intermolecular interaction energies with a novel graphical representation of their magnitude. In this manner intriguing questions, such as why some crystals bend with an applied force while others break, and why one polymorph of a drug exhibits exceptional tabletability compared to others, can be addressed in terms of the anisotropy of the topology of pairwise intermolecular interaction energies. This approach is applied to a sample of organic molecular crystals with known bending, shearing and brittle behaviour, to illustrate its use in rationalising their mechanical behaviour at a molecular level.